2008
DOI: 10.1177/0731684408096428
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Aluminum — Fly-Ash Composite Produced by Impeller Mixing

Abstract: The present investigation is focused on the utilization of abundantly available industrial waste, i.e., fly-ash in a useful manner by dispersing it into aluminum/aluminum—magnesium matrix to produce composites by a liquid metallurgy route. Composites are produced with different percentage of reinforcing phase. Further, these composites are characterized using XRD, wet chemical analysis, and image analysis. Mechanical and wear properties of the composites are evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Manufacturing aspects of particle reinforced composite components has been investigated by few researchers pertaining to machining studies of particle reinforced cast aluminum composites followed by liquid metallurgy route. [1][2][3][4][5][6] discussed the application of Metal matrix composites in manufacturing of transportation vehicles. M.K.Surappa, [7] carried out research work on the manufacturing aspect of the particulate metal matrix composites and he observed the need of improving damage tolerant properties particularly fracture toughness and ductility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Manufacturing aspects of particle reinforced composite components has been investigated by few researchers pertaining to machining studies of particle reinforced cast aluminum composites followed by liquid metallurgy route. [1][2][3][4][5][6] discussed the application of Metal matrix composites in manufacturing of transportation vehicles. M.K.Surappa, [7] carried out research work on the manufacturing aspect of the particulate metal matrix composites and he observed the need of improving damage tolerant properties particularly fracture toughness and ductility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Decrease in interfacial energy is assured by having interfacial reaction to occur and producing reaction production like Mg 2 Si [8]. Addition of Mg into the liquid metal reduces the surface tension [9] and there by avoids the rejection of the particles from the melts. Without addition of Mg recovery of the particles into the melt is quite low.…”
Section: Introductionmentioning
confidence: 99%
“…Results have shown that the foam-like behavior of aluminum/ fl y ash cenosphere composites leads to high compressive strain and the possibility of tailoring the strength and modulus. [8][9][10][11] Young's modulus, yield strength, and plateau stress of syntactic foams increased with composite density, 7,9,12 but the energy absorption ability increased when the cenosphere volume fraction is increased. 8,13 Two existing studies have focused on determining the strain rate effects on mechanical properties of aluminum matrix syntactic foams.…”
mentioning
confidence: 96%